2019
DOI: 10.1111/sjop.12601
|View full text |Cite
|
Sign up to set email alerts
|

Does cyberbullying predict internalizing problems and conduct problems when controlled for traditional bullying?

Abstract: In this study, relations between cybervictimization and internalizing and conduct problems were analyzed while controlling for traditional victimization. A sample of 701 emerging adults in secondary vocational education completed self‐reports about cybervictimization, traditional victimization, internalizing problems and conduct problems. Using multiple regression analyses with heteroscedasticity‐consistent estimates, it was found that cybervictimization is related to internalizing and conduct problems while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…A review of literature on this topic concluded that cyberbully is prevalent on the Internet and some 11.2% to 56.9% of Chinese adolescents reported experiences of cyberbullying victimization, the second-highest median rate among nine nations surveyed in the study [31]. Similar to traditional bullying, cyberbullying as a victim via social media is founded to be closely related to a series of behavioral and psychological problems (e.g., depression, anxiety, post-traumatic stress disorder, and suicidal ideation) [32,33]. Cyberbullying victimization has also been found to reduce individuals' self-esteem [34] and make them feel less inclined to engage with social media platforms and online communities [35], thus decreasing online social support from peers, friends, and family members.…”
Section: Introductionmentioning
confidence: 93%
“…A review of literature on this topic concluded that cyberbully is prevalent on the Internet and some 11.2% to 56.9% of Chinese adolescents reported experiences of cyberbullying victimization, the second-highest median rate among nine nations surveyed in the study [31]. Similar to traditional bullying, cyberbullying as a victim via social media is founded to be closely related to a series of behavioral and psychological problems (e.g., depression, anxiety, post-traumatic stress disorder, and suicidal ideation) [32,33]. Cyberbullying victimization has also been found to reduce individuals' self-esteem [34] and make them feel less inclined to engage with social media platforms and online communities [35], thus decreasing online social support from peers, friends, and family members.…”
Section: Introductionmentioning
confidence: 93%
“…In recent work, 42% of adolescents reported being called offensive names online, while 32% reported having a rumour spread about them (Pew Research Center, 2018b). Experiencing cybervictimization (i.e., intentional acts of aggression committed through means of social technologies; Álvarez‐García et al, 2017) has been connected to a plethora of adverse social, emotional, behavioural, and academic outcomes for adolescents (Marciano et al, 2020; Nixon, 2014), with cybervictimization predicting depression, suicide, and social anxiety over and above in‐person victimization (Bonanno & Hymel, 2013; van Geel & Vedder, 2020; Wigderson & Lynch, 2013).…”
Section: Communicationmentioning
confidence: 99%
“…Little research has been conducted on Pakistan's hotel industry and the effects of information and technology on employees [11] (Khan et al, 2021). The concept of WCB has started to attract researchers' attention [12][13][14] as a recently recognized risk factor in the workplace. The hotel industry has always been marked with high job demand and violence [14].…”
Section: Introductionmentioning
confidence: 99%